ANALISIS PENGARUH SISTEM INFORMASI AKUNTANSI PENJUALAN DAN MINAT MERCHANT DALAM e-TRANSAKSI TERHADAP PENGIMPLEMENTASIAN TRANSAKSI ELEKTRONIK GOPAY - Thennica, Gella; Ruben Manullang, Rizal; Maharani, Yunita (STIE IBEK Pangkalpinang, 2021)
This thesis was written and compiled by Gella Thennica with student identification number 130170017, entitled in Bahasa Indonesia “Analisis Pengaruh Sistem Informasi Akuntansi Penjualan dan Minat Merchant Dalam e-Transaksi Terhadap Pengimplementasian Transaksi Elektonik Gopay”. Conducted by conducting surveys to Gopay merchants. The research objective is to see whether there is an effect of Sales and Merchant Accounting Information Systems in E-transactions on the Implementation of Gopay. The theories used in this study are Accounting theory, Art Accounting theory, Accounting Information Systems theory, Interest theory and Utilization Studies. The research method used in this research is a survey method. The research respondents were 22 merchants using Gopay e-transactions. The variables used are the Sales Accounting Information System and Merchant Interest in E-transactions as an independent variable and the implementation of Gopay e-Transactions as the dependent variable. This study uses quantitative analysis of descriptive primary data from direct research in the field. As a toolin statistical data using the JASP Version 0.9.2.0. Universiteit-Van-Amsterdam program. Based on the results of the study that : (1) There is a no influence of the Sales Accounting Information System on the implementation of the Gopay e-Transaction, this is evidenced by the value of tcount (2.067) < ttable (2.09302). (2) There is a significant influence of the merchant interest variable in E-transactions on the implementation of the Gopay e-Transaction. This is evidenced by the value of tcount (6.584)> ttable (2.09302). (3) There is a significant effect of the Sales Accounting Information System and Merchant Interest in e-Transactions on the Implementation of Gopay e-Transactions. This is evidenced by Fcount (21,890) > Ftable (4.38).